O lambari Astyanax altiparanae (Characidae) pode ser um dispersor de sementes? - Gomiero, Leandro Muller [UNESP]; De Souza Braga, Francisco Manoel [UNESP] (Universidade Estadual de Maringa, 2003)
This work characterized the feeding of Astyanax altiparanae in the sub-basin of Corumbataí river and in the basin of Jacaré-pepira river with a focus on the ingestion of Croton urucurana seeds. The food items of Astyanax altiparanae were, in decreasing APD (Alimentary Preference Degree) order: allochthonous insects, allochthonous plant material, Croton urucurana seeds, autochthonous insects, sediments, autochthonous plant material, scales, oocytes and arachnidans. Croton urucurana seeds occurred during the summer, in the flood period. Lambari, Astyanax altiparanae, could be a secondary disperser of Croton urucurana seeds, however, the intensity and effectiveness of this dispersion may be still investigated.
Can lambari, Astyanax altiparanae (Characidae), be a seed disperser?
Keywords: Astyanax altiparanae; Croton urucurana; Disperser; Natural feeding; Seeds; Croton; ecology; feeding behavior; fish; floodplain; nonhuman; plant seed; river; seed dispersal; Hexapoda